PENGGUNAAN MEDIA PEMBELAJARAN BERBASIS ICT DI SMAN 1 SIDAMANIK KABUPATEN SIMALUNGUN - Tiarma Intan Marpaung; Bloner Sinurat; Melda Veby Ristella Munthe; David Togi Hutahaean; Christian Neni Purba; Rianita Simamora (Jurnal Abdimas Bina Bangsa, 2023)
This community service was held to enhance the use of Information Technology and Communication (ICT) among teachers in SMA Negeri 1 Sidamanik Simalungun regency North Sumatera as media to teach students in the class. This issue is important to be solved in order to the development of new era nowadays where every aspects of life has use technology. This community service was held hybrid, one day of offline training and then followed by online training. As the result, teachers of SMA Negeri 1 Sidamanik did a positive progress on the development of ICT use. It is hoped that workshop alike can be done in the larger scope and length of time in the future